Anticipation of Relapse and Acute Graft-Versus-Host Disease after Allogeneic Peripheral Blood Stem Cell Transplantation: The Fundamental Role of Antigen-Presenting (Dendritic) Cells - Nasif KA; Al Samghan AS; El-Sharkawy N; Abass AM; Elgezawy E; Khaled SAA; Elbadry MI; Thabet MM (Dove Medical Press, 2022)
Khalid Ali Nasif,1,2 Awad S Al Samghan,3 Nahla El-Sharkawy,4 Amr M Abass,5 Ebtesam Elgezawy,6,7 Safaa AA Khaled,8 Mahmoud I Elbadry,9 Marwa M Thabet6 1Clinical Biochemistry Department, College of Medicine, King Khalid University, Abha, Saudi Arabia; 2Biochemistry Department, Faculty of Medicine, Minia University, Minia, Egypt; 3Family and Community Medicine Department, College of Medicine, King Khalid University, Abha, Saudi Arabia; 4Clinical Pathology Department, National Cancer Institute, Cairo University, Cairo, Egypt; 5Medical Physiology Department, College of Medicine, King Khalid University, Abha, Saudi Arabia; 6Clinical Pathology Department, Faculty of Medicine, Assiut University, Assiut, Egypt; 7Immunohematology Consultant, AMCH, Asir, Saudi Arabia; 8Department of Internal Medicine, Clinical Hematology Unit, AUH/Unit of Bone Marrow Transplantation, South Egypt Cancer Institute, Faculty of Medicine, Assiut University, Assiut, Egypt; 9Department of Internal Medicine, Division of Haematology, Faculty of Medicine, Sohag University, Sohag, EgyptCorrespondence: Safaa AA Khaled, Department of Internal Medicine, Clinical Hematology Unit, AUH/Unit of Bone Marrow Transplantation, South Egypt Cancer Institute, Faculty of Medicine, Assiut University, Assiut, Egypt, Email safaakhaled2003@gmail.com; safaakhaled@aun.edu.eg Mahmoud I Elbadry, Department of Internal Medicine, Division of Haematology, Faculty of Medicine, Sohag University, Sohag, Egypt, Tel +20 10-6596-4083, Fax +20 93-460-9304, Email mahmoudibrahem837@gmail.com; mahmoudibrahim@med.sohag.edu.egBackground: Dendritic cells (DCs) are antigen-presenting cells. In humans two distinct lineages of DCs exist: DC1 and DC2. Efforts to explore the role of DCs in acute graft-versus-host disease (aGVHD) after allogeneic peripheral blood stem–cell transplantation (PBSCT) are gaining traction. However, further research is needed to identify particular lineages and their values in terms of developing an evidence-based aGVHD- or relapse-prevention strategy. We monitored DC counts and subsets in PBSC grafts while harvesting stem cells in recipients to elucidate their value in anticipating disease relapse or aGVHD.Methods: We enrolled 29 participants. Using fluorescence-activated cell sorting, total counts/kg of CD34+, DCs, and DC subsets were analyzed in 29 PBSC-graft components using CMRF44, CD11c, and CD4 monoclonal antibodies (MoAbs).Results: In the 29 grafts, we detected a significant positive correlation (P< 0.01) between DCs and both DC1 and DC2. Significantly higher counts (P< 0.01) of DCs and DC1 in those who had developed aGVHD (nine cases) were also observed. Relapsed cases (two) were also associated with higher counts of DCs and DC2. A significant positive correlation (P< 0.05), was recorded between DCs and DC1 counts and the day of myeloid engraftment, while this was not detected on the day of platelet engraftment. Myeloid engraftment transpired earlier in patients without aGVHD. Increased DC-graft numbers, particularly DC1 measured by CD11c Moabs, were associated with aGVHD. Recipients of higher numbers of CD4bright DCs had an increased risk of relapse after allogeneic PBSCT.Conclusion: This study analyzed DCs in PBSC grafts, using novel specific MoAbs and flow cytometry. Our data showed that higher donor DC1 counts were linked to the incidence of aGVHD and DC2 with relapse. We propose a fundamental role for DC-graft monitoring in anticipating aGVHD and disease relapse.Keywords: dendritic, cell, biomarker, acute GVHD, relapse, allogeneic PBSCT